Validity and Reliability Reporting Practices in the Field of Health Education and Behavior: A Review of Seven Journals. (February 2014) - Barry, Adam E.; Chaney, Beth; Piazza-Gardner, Anna K.; Chavarria, Enmanuel A.
Health education and behavior researchers and practitioners often develop, adapt, or adopt surveys/scales to quantify and measure cognitive, behavioral, emotional, and psychosocial characteristics. To ensure the integrity of data collected from these scales, it is vital that psychometric properties (i.e., validity and reliability) be assessed. The purpose of this investigation was to (a) determine the frequency with which published articles appearing in health education and behavior journals report the psychometric properties of the scales/subscales employed and (b) outline the methods used to determine the reliability and validity of the scores produced. The results reported herein are based on a final sample of 967 published articles, spanning seven prominent health education and behavior journals between 2007 and 2010. Of the 967 articles examined, an exceedingly high percentage failed to report any validity (ranging from 40% to 93%) or reliability (ranging from 35% to 80%) statistics in their articles. For health education/behavior practitioners and researchers to maximize the utility and applicability of their findings, they must evaluate the psychometric properties of the instrument employed, a practice that is currently underrepresented in the literature. By not ensuring the instruments employed in a given study were able to produce accurate and consistent scores, researchers cannot be certain they actually measured the behaviors and/or constructs reported.